An optimised sorghum brewing process - Holmes, Calum P. (2015)
Whilst there is a tradition of indigenous opaque sorghum beer production in Africa, the manufacture of Western-style clarified lager beers from sorghum is a relatively recent development, originating in late 1980’s Nigeria. There remains substantial scope to optimise the process by tailoring the equipment and conditions utilised more specifically to the raw material. This was the context to the main objectives of this PhD project: towards an improved sorghum brewing process. Two principal approaches were employed: 1. The reduction of primary energy usage by developing novel modifications to the mashing and wort boiling unit operations and 2. Characterisation of the material properties of a substantial co-product of sorghum brewing, sorghum spent grains (SSG) as a pre-requisite to assessing its suitability for the production of value-added products and/or biofuel.